2016
DOI: 10.1002/mats.201600040
|View full text |Cite
|
Sign up to set email alerts
|

Use of Kirkwood-Buff Integrals for Extracting Distinct Diffusion Coefficients in Macromolecule-Solvent Mixtures

Abstract: The possibility to extract velocity correlation quantities from fluctuation thermodynamic properties is explored in the case of macromolecule–solvent mixtures. Indeed, Kirkwood–Buff integrals, Gij, together with self‐diffusion and viscosity data can provide an approximation for distinct diffusion coefficients (DDCs), Ddij. Herein, Ddij for binary polyethyleneglycol (PEG)(i)–water(0) systems is calculated. These systems show positive values of Ddii coefficients, indicating strong PEG–PEG interaction, and provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
(126 reference statements)
0
1
0
Order By: Relevance
“…[14][15][16] In addition, the SEEq does not include important effects as the intermolecular interactions between molecules of solute and between molecules of solvent and solute, being this an aspect that is very important in the study of diffusion through a heterogeneous system. [14][15][16]18] Several strategies based on models and simulations have being developed for the study of Di among which are included: simulation based on molecular dynamics into equilibrium and non-equilibrium states, simulation based on the Maxwell-Stefan approach including models as Darken-Type Models and Vignes-Type Models, [13,19,20] and thermodynamic methods based on to Kirkwood-Buff integrals in finite systems, scaling of small system fluctuations or Kirkwood-Buff integrals. [21,22] It has been indicated that more than 100 different mathematical models for the description and study of mass transfer in liquid membranes have been proposed between 1980 to 1995 alone; [23] but, at the same time, several authors have recognized and criticized the excessive use of procedures based on advanced mathematics, since the physical significance of the parameters involved is not absolutely understood in many case.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] In addition, the SEEq does not include important effects as the intermolecular interactions between molecules of solute and between molecules of solvent and solute, being this an aspect that is very important in the study of diffusion through a heterogeneous system. [14][15][16]18] Several strategies based on models and simulations have being developed for the study of Di among which are included: simulation based on molecular dynamics into equilibrium and non-equilibrium states, simulation based on the Maxwell-Stefan approach including models as Darken-Type Models and Vignes-Type Models, [13,19,20] and thermodynamic methods based on to Kirkwood-Buff integrals in finite systems, scaling of small system fluctuations or Kirkwood-Buff integrals. [21,22] It has been indicated that more than 100 different mathematical models for the description and study of mass transfer in liquid membranes have been proposed between 1980 to 1995 alone; [23] but, at the same time, several authors have recognized and criticized the excessive use of procedures based on advanced mathematics, since the physical significance of the parameters involved is not absolutely understood in many case.…”
Section: Introductionmentioning
confidence: 99%